Visualizing “Moorish” traces within Spain: Orientalism and medievalist nostalgia in Spanish colonial photojournalism 1909–33 - Bolorinos Allard, E (Routledge, 2017)
During the Spanish colonization of Morocco (1912–56), Spanish cultural discourses represented Morocco as a civilization with significant ties to Spain and explored the influences of Spain’s Islamic medieval past on Spanish culture and society. Because the colonial campaigns coincided with the development of photojournalism in Spain, the discourse of a Spanish-Moroccan fraternity was expressed in visual form in the press with a plethora of photographs, which evoked the “Moorish trace” in Spain. This article examines photographs of women and urban spaces in Morocco and Spain as key subjects chosen to represent this trace in photojournalism. It focuses on a number of widely-read photographic magazines between 1909 and 1933, including La Esfera, Mundo gráfico, Nuevo mundo, Estampa, and Ahora, and the colonial military publication Revista de tropas coloniales. The article argues that photographs of urban spaces in Morocco and Spain served to evoke the memory of Islamic civilization, while images of women served to embody its ethnic and cultural legacy within Spain. It shows how colonial photography was used to recreate a medieval Muslim Iberian past that had long vanished, acting as a vehicle for the medievalist nostalgia that permeated Spanish culture during this period. Ultimately, the article reveals that Spanish colonial photojournalism orientalized not only North African culture but also Spain itself.